Exploring the risk factors of early sepsis after liver transplantation: development of a novel predictive model - Chen, Wanting; Wu, Shengdong; Gong, Lingwen; Guo, Yu; Wei, Li; Jin, Haoran; Zhou, Yan; Li, Chuanshuang; Lu, Caide; Xu, Lanman (Frontiers in Medicine, 2023)
Background Sepsis is a severe and common complication of liver transplantation (LT) with a high risk of mortality. However, effective tools for evaluating its risk factors are lacking. Therefore, this study identified the risk factors of early post-liver transplantation sepsis and established a nomogram. Methods We analyzed the risk factors of post-liver transplantation sepsis in 195 patients. Patients with infection and a systemic inflammatory response syndrome (SIRS) score ≥ 2 were diagnosed with sepsis. The predictive indicators were screened with the least absolute shrinkage and selection operator (LASSO) and collinearity analyses to develop a nomogram. The prediction performance of the new nomogram model, Sequential Organ Failure Assessment (SOFA) score, and Modified Early Warning Score (MEWS) was compared through assessment of the area under the curve (AUC), decision curve analysis (DCA), net reclassification index (NRI), and integrated discrimination improvement (IDI). Results The nomogram was based on postoperative heart rate, creatinine concentration, PaO2/FiO2 ratio < 400 mmHg, blood glucose concentration, and international normalized ratio. The AUC of the nomogram, the SOFA score, and MEWS were 0.782 (95% confidence interval CI: 0.716–0.847), 0.649 (95% CI: 0.571–0.727), and 0.541 (95% CI: 0.469–0.614), respectively. The DCA curves showed that the net benefit rate of the nomogram was higher than that of the SOFA score and MEWS. The NRI and IDI tests revealed better predictive performance for the nomogram than SOFA score and MEWS. Conclusion Heart rate, creatinine concentration, PaO2/FiO2, glucose concentration, and international normalized ratio should be monitored postoperatively for patients at risk of post-liver transplantation sepsis. The nomogram based on the aforementioned risk factors had a better predictive performance than SOFA score and MEWS.